Overview on Organic and Inorganic Materials Used for Furniture and Its Decorations - SALCA Emilia-Adela (BOOKPI INTERNATIONAL, 2022)
Natural materials contributed to the development of human life on Earth. These materials have been used for more than 10,000 years. Raw wood or stone have been used for specific purposes and functions, including furniture. Over the centuries the human creativity led to the creation of different types of furniture and decorations. This chapter represents a synthesis of various organic and inorganic materials used for art furniture decorations. Synthetic classifications of the basic materials, as well as specific materials for furniture are compiled. Out of their large variety, selected natural materials are here approached, such as wood, gold, silver, tin, brass, amber, ivory, tortoiseshell and nacre. A specific format is applied to each one of the materials providing information about the structure, classification, identification, properties, and substitutes.
Natural materials contributed to the development of human life on Earth. These materials have been used for more than 10,000 years. Raw wood or stone have been used for specific purposes and functions, including furniture. Over the centuries the human creativity led to the creation of different types of furniture and decorations. This chapter represents a synthesis of various organic and inorganic materials used for art furniture decorations. Synthetic classifications of the basic materials, as well as specific materials for furniture are compiled. Out of their large variety, selected natural materials are here approached, such as wood, gold, silver, tin, brass, amber, ivory, tortoiseshell and nacre. A specific format is applied to each one of the materials providing information about the structure, classification, identification, properties, and substitutes.